A study on the emotional intelligence among teaching faculty of a medical college in South Karnataka - Raman Hulinaykar; Kusuma Achalkar; Ningangouda Parvatagouda; M M Angadi (Wolters Kluwer Medknow Publications, 2021)
Introduction: Doctors have multiple roles to play in the society. The emotional intelligence (EI) of medical college teachers plays a decisive role on the outcome of medical students. Teachers with good EI will create a learning environment that encourages positive social interaction, active encouragement, and motivation to learn among students. Objectives: The objective of the study is to assess the level of EI and the influence of sociodemographic variables on it among teaching faculties of a medical college. Materials and Methods: A cross-sectional study was conducted using self-report EI questionnaire scale. The data were analyzed and expressed in percentages and proportions. Mean, standard deviation, and statistical significance were calculated, wherever necessary. Results: More than half of the teaching faculty showed average EI (66.67%) and 8.33% had poor EI. The social skills of teaching faculty showed positive correlation and statistical significance with teaching experience. Conclusion: There is a need to take appropriate steps to improve the EI of teaching faculties by the institutions as it has an impact on the outcome of learner doctors.